2006
DOI: 10.1109/tnano.2006.885035
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the TiN Gate Electrode With Tunable Work Function and Its Application for FinFET Fabrication

Abstract: The titanium nitride (TiN) gate electrode with a tunable work function has successfully been deposited on the sidewalls of upstanding Si-fin channels of FinFETs by using a conventional reactive sputtering. It was found that the work function of the TiN ( TiN ) slightly decreases with increasing nitrogen (N 2 ) gas flow ratio, = N 2 (Ar + N 2 ) in the sputtering, from 17% to 100%. The experimental threshold voltage ( th ) dependence on the shows that the more offers the lower th for the TiN gate n-channel FinFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 31 publications
5
63
0
4
Order By: Relevance
“…The further increase of N 2 /(N 2 + Ar) until 0.167 did not influence the TiN work function significantly. On the contrary, Liu et al reported that the TiN work function was also decreased (from 4.82 to 4.71 eV) with the increase of N 2 /(N 2 + Ar) ratio from 0.17 to 0.83, which is in good agreement with our results (see Fig. ).…”
Section: Resultssupporting
confidence: 93%
“…The further increase of N 2 /(N 2 + Ar) until 0.167 did not influence the TiN work function significantly. On the contrary, Liu et al reported that the TiN work function was also decreased (from 4.82 to 4.71 eV) with the increase of N 2 /(N 2 + Ar) ratio from 0.17 to 0.83, which is in good agreement with our results (see Fig. ).…”
Section: Resultssupporting
confidence: 93%
“…[1][2][3][4][5] As a functional CMOS circuit, a static random access memory (SRAM) has actively been developed using the PVD-TiN gate FinFETs owing to the symmetrical V th . [6][7][8] However, the metal gate material such as a TiN could cause V th variations owing to its grain granularity, and metal grainorientation effects induce a work function variation (WFV).…”
Section: Introductionmentioning
confidence: 99%
“…2(e) and 2(j). The CG electrodes were also patterned by EB lithography and fabricated using a combination of inductively coupled plasma (ICP) RIE for n + -poly-Si and wet etching for PVD-TiN (33)(34)(35). The three types of devices obtained are referred to as TF-ONO, TF-ANO, and RF-ANO SOI-FinFET flash memories.…”
Section: Device Fabricationmentioning
confidence: 99%